Heterogenously‐expressed chitosanase combining a green ball milling method for enzymatic degradation. Issue 1 (5th April 2022) - Su, Haipeng; Sun, Jianan; Guo, Chaoran; Jia, Zhenrong; Mao, Xiangzhao
Abstract: Chitooligosaccharides (COSs) and d ‐glucosamine (GlcN), the most valuable biomolecules due to their various physiological functions, can be available inexpensively from chitosan by bio‐enzymatic degradation, in which chitosanases play a key role. On the other hand, pretreatment of chitosan is the necessary procedure in the bioproduction by enzymatic hydrolysis. Therefore, the green and efficient pretreatment strategy as well as superior enzyme activity are the most critical aspects in scaled up production. This study investigated environmentally friendly and efficient enzymatic hydrolysis of powdery chitosan (PC) pretreated by ball‐milling. First, heterologous expression yielded OUC‐CsnPT, a glycoside hydrolase family 46 chitosanase with a predominant specific activity of 5346.56 U/mg at pH 6.0°C and 45°C. The endo‐type chitosanase OUC‐CsnPT hydrolyzed chitosan to produce GlcN and chitobiose [(GlcN)2 ]. Then, ball‐milling was employed to pretreat PC to promote chitosanase OUC‐CsnPT hydrolysis, and the effectiveness was characterized by scanning electron microscope, X‐ray diffraction, and FTIR‐attenuated total reflection. Through the development of the novel route, the yield of COSs and GlcN for ball‐milling powdery chitosan increased by 10.8‐folds with a concentration of 14.5 μmol/ml. Hence, this technique presents a promising strategy suited to be a straightforward and environmentally friendly option for oligosaccharides production, broadening the theoretical basis for PC biodegradation. Abstract : Ball milling pretreatment significantly reduced the crystallinity of chitosan substrate and enhanced the enzyme accessibility. Heterogenouslyexpressed highly active chitosanase OUC‐CsnPT efficiently degraded chitosan to prepare glucosamine and chitobiose combining green ball milling method.